2022
DOI: 10.1136/flgastro-2022-102168
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab for the treatment of moderate to severe ulcerative colitis: a multicentre UK cohort study

Abstract: ObjectiveUstekinumab is an interleukin-12/interleukin-23 receptor antagonist licensed for the treatment of ulcerative colitis (UC). Clinical trial data were promising; however, real-world data are limited. We assessed the safety and effectiveness of ustekinumab in UC in a real-world setting.Design/methodThis was a multicentre, retrospective, observational cohort study between February 2020 and January 2022. Disease activity was assessed using the Simple Clinical Colitis Activity Index (SCCAI). Clinical remissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…In all, 11 studies [6][7][8][9]16,19,20,[22][23][24]26 Between-study heterogeneity was considerable at week 8 (I 2 = 87%) and month 12 (I 2 = 82%), might be not important at weeks 12-16 (I 2 = 26%), and was substantial at month 6 (I 2 = 65%) (Figure 1).…”
Section: Primary Endpoint: Clinical Remissionmentioning
confidence: 98%
See 4 more Smart Citations
“…In all, 11 studies [6][7][8][9]16,19,20,[22][23][24]26 Between-study heterogeneity was considerable at week 8 (I 2 = 87%) and month 12 (I 2 = 82%), might be not important at weeks 12-16 (I 2 = 26%), and was substantial at month 6 (I 2 = 65%) (Figure 1).…”
Section: Primary Endpoint: Clinical Remissionmentioning
confidence: 98%
“…Of the 254 citations identified, 19 studies including 3786 patients with UC were eligible for inclusion in this systematic review (Table S2). [5][6][7][8][9][15][16][17][18][19][20][21][22][23][24][25][26][27][28] In all, 13 studies were reported as full-text articles, and 6 were conference proceedings. According to JBI criteria for quality assessment, 14 studies showed low risk of bias, and 5 articles showed moderate risk (Table S3).…”
Section: Re Sultsmentioning
confidence: 99%
See 3 more Smart Citations